U-Pb geochronology and Hf isotopes of the Grenvillian Río Hondo gneisses, Puebla: redefining the western edge of Oaxaquia - Luigi A. Solari; Mariano Elías Herrera; Guillermo Espejo-Bautista; Mariana Jaramillo-Jaramillo; María del Consuelo Macías Romo; Carlos Ortega-Obregón (Revista Mexicana de Ciencias Geológicas)
In situ Río Hondo (Puebla, southern Mexico) gneiss samples, as well as clastic samples recovered from the nearby-outcropping latest Paleozoic Matzitzi Formation, a fluvial unit mainly sourced by Grenvillian rocks,  were historically interpreted as representative of the northernmost exposures of the Oaxacan Complex, the largest outcrop of ortho and metasedimentary units, made up of mostly 1.0–1.3 Ga protoliths, affected cfby local migmatization (ca. 1.1 Ga) and granulite facies metamorphism at ca. 0.98 Ga, constituting the most prominent outcrop of the Oaxaquia microcontinent.